Fire Responses to the 2010 and 2015/2016 Amazonian Droughts - Silva Junior, Celso H. L.; Anderson, Liana O.; Silva, Alindomar L.; Almeida, Catherine T.; Dalagnol, Ricardo; Pletsch, Mikhaela A. J. S.; Penha, Thales V.; Paloschi, Rennan A.; Aragão, Luiz E. O. C. (Frontiers in Earth Science, 2019)
Extreme droughts in Amazonia cause anomalous increase in fire occurrence, disrupting the stability of environmental, social and economic systems. Thus, understanding how droughts affect fire patterns in this region is essential for anticipating and planning actions for remediation of possible impacts. Focused on the Brazilian Amazon biome, we investigated fire responses to the 2010 and 2015/2016 Amazonian droughts using a remote sensing data. Our results revealed that the 2015/2016 drought surpassed the 2010 drought in intensity and extent. During the 2010 drought, we found a maximum area of 846,800 km2 (24% of the Brazilian Amazon biome) with significant (p<0.05) rainfall decrease in the first trimester, while during the 2015/2016 the maximum area reached 1,702,800 km2 (47% of the Brazilian Amazon biome) in the last trimester of 2016. On the other hand, the 2010 drought had a maximum area of 840,400 km2 (23% of the Brazilian Amazon biome) with significant (p<0.05) land surface temperature increase in the first trimester, while during the 2015/2016 drought the maximum area was 2,188,800 km2 (61% of the Brazilian Amazon biome) in the last trimester of 2015. Unlike the 2010 drought, during the 2015/2016 drought, significant positive anomalies of active fire and CO2 emissions occurred mainly during the wet season, between October 2015 and March 2016. During the 2010 drought positive active fire anomalies resulted from the simultaneous increase of burned forest, non-forest vegetation and productive lands. During the 2015/2016 drought, however, this increase was dominated by burned forests. The two analysed droughts emitted together 475 Tg CO2, with 233 Tg CO2 in 2010, 147 Tg CO2 in 2015 and 95 Tg CO2 in 2016, which represented respectively 209%, 136%, 82% of the Brazil’s national targets for reducing carbon emissions from deforestation by 2020 (1288 Tg CO2 from 1996-2005 average deforestation or a rate of 0.11 Pg CO2 year-1). Finally, we anticipate that the increase of fires during the droughts showed here may intensify and can become more frequent in Amazonia due to changes in climatic variability if no regulations on fire use are implemented.